Vitamin D deficiency prevalence among healthy term infants at the age of 4–6 months: A cross-sectional observational study from tertiary care hospital setting - Uma Devi Karuru; Bhavneet Bharti; Sanjay Verma; Naresh Sachdeva (Indian Journal of Child Health, 2021)
Background: Role of Vitamin D has expanded from bone health to a myriad of physiological and pathological conditions in humans. Although guidelines recommend supplementation of Vitamin D in infants, evidence for healthy term infants at 4–6 months is limited in Indian settings. Objectives: The objectives of the study were to estimate the prevalence of Vitamin D deficiency and its risk factor in healthy term infants at 4–6 months of age before initiation of complementary feeding. Materials and Methods: Four–six-month-old infants (n = 93) were enrolled. The healthy term infants >37 weeks, birth weight >2.5 kg with no diagnosed medical disorders in the mother or baby, and not on Vitamin D supplementation were included. Levels of calcium, phosphorus, alkaline phosphatase, parathormone, and Vitamin D were also assessed. Results: The prevalence of Vitamin D deficiency (25OHD ? 20 ng/ml) and insufficiency (20–30 ng/ml) was 76.3% and 15.05%, respectively, with a mean (SD) 25(OH) D level of 13.42 ± 10.08 ng/ml and median level of 11.58 ng/ml. On multivariate analysis, rural children continued to have lower odds of severe Vitamin D deficiency (? 5 ng/ml) as compared to urban children (OR 0.18; 95% CI: 0.03–0.92) (P = 0.04). In addition, odds of severe Vitamin D deficiency (?5 ng/ml) increased significantly by 20% for everyone unit increase in socioeconomic score by Kuppuswamy (modified) (OR 1.20; 95% CI: 1.04–1.40, P = 0.01). Conclusions: High level of Vitamin D insufficiency in our study among apparently healthy infants with uncomplicated antenatal and neonatal period clearly supports current guidelines for daily supplementation of Vitamin D for infants and children for optimizing their Vitamin D levels and preventing complications.